Intranatal and postnatal care practices among married women of reproductive age group: a community based cross- sectional study in the rural area of Surendranagar district - Bhimani, Nishant R.; Vachhani, Pushti V.; Kartha, Girija P. (International Journal Of Community Medicine And Public Health, 2017)
Background: Intra natal care means care taken during delivery. This consists of taking care of not only the mother but also the newborn at the time of child-birth. Appropriate delivery care is crucial for both maternal and perinatal health. Increasing skilled attendance at birth is a central goal of the safe motherhood and child survival mission. Postpartum care aimed at complication-free puerperium and a healthy baby. There is a high risk of mortality for both the mother and her baby in the immediate period around birth. High quality intranatal and postnatal care is the important way to reduce the maternal morbidity and mortality. Utilization of intranatal and postnatal services is poor in the rural areas, which ultimately lead to increased maternal & child morbidity and mortality. Methods: The study was carried out among married women of reproductive age group. Pre-designed and pretested Performa was used to obtain the information from participants. It was community based cross - sectional study. All the collected data were analysed by applying appropriate statistical tests. The data were analysed by statistical package for social sciences (SPSS). Results: A total of 353 women were included in the study. Majority (86.97%) of women utilized health facility either government or private for their deliveries. Significant difference was observed between literacy status as well as socio economic class and utilization of institutional facility for the place of delivery. More than half women i.e. nearly 56% had not availed postnatal care services. Conclusions: Percentage of institutional deliveries as well as deliveries attended by skilled birth attendant was quite better. The most common reason for not availing the intra natal and postnatal services was found to be lack of knowledge regarding importance of these services on the outcome of delivery.